Local Wisdom-Based Parenting Concept in Stunting Prevention Policy among Coastal Bugis Communities - Andi Surahman Batara; Linda Hardianti Saputri; Nurul Hikmah B (Journal of Public Health and Pharmacy, 2026)
Introduction: Stunting remains a major public health issue in Indonesia, particularly in coastal areas such as Barru District, South Sulawesi, which has shown a significant increase in prevalence. Parenting practices play a central role in stunting prevention; however, existing policies often fail to accommodate the local values embedded within communities. Among coastal Bugis communities, local wisdom-based parenting practices such as mattarana’ and yabelale are believed to contribute to the holistic development of children, yet they have rarely been studied in the context of health policy. This study aims to explore the concept of local wisdom-based parenting within Bugis coastal communities and to analyze its potential for integration into more contextual and participatory stunting prevention policies. Methods: A mixed-methods sequential exploratory design was employed with explicit qualitative–quantitative integration. The qualitative phase generated culturally grounded constructs of parenting through in-depth interviews, focus group discussions, and participatory observations with parents, community leaders, health workers, and posyandu cadres. These findings directly informed the development of quantitative survey instruments. The subsequent quantitative phase involved a descriptive survey of 326 caregivers selected via stratified random sampling. Integration occurred at the design level (instrument development), the methods level (sequential linkage), and the interpretation level, where qualitative themes were used to contextualize quantitative results. Data were analyzed using thematic analysis and descriptive statistics. Ethical approval was obtained from the Health Research Ethics Committee of Maluku Husada School of Health Sciences (RK.196/KEPK/STIK/VII/2025). Results: Qualitative findings revealed that mattarana’ is understood as a form of intensive maternal caregiving, while yabelale represents a spiritual-emotional practice that strengthens mother-child attachment. Quantitative data indicated that 93.3% of respondents had adequate knowledge about stunting and 99.4% demonstrated positive attitudes toward healthy parenting. However, parenting practices did not fully reflect this knowledge. Furthermore, 62.9% of respondents agreed that local wisdom should be integrated into stunting prevention policies. Integrated analysis indicates that local values shape how biomedical knowledge is interpreted and enacted in daily caregiving. Conclusion: Integrating the concept of mattarana’ into stunting prevention policies may enhance the effectiveness of interventions through a more culturally grounded, socially responsive, and locally contextualized approach. This strategy supports WHO’s whole-of-society principle and offers a more humanistic and sustainable framework for health development.